Integration of Digital Literacy and Religious Literacy in Islamic Education Curriculum - Adam Adam; Surtimah Surtimah; Nuritam Nuritam; Nasaruddin Nasaruddin; Ilham Ilham (al-Afkar, Journal For Islamic Studies, 2026)
This study aims to analyze the concepts, principles, and implementation of the integration of digital literacy and religious literacy in Islamic Religious Education (PAI) learning materials. The method used was library research. Research data were obtained by reviewing various relevant literature sources, such as books and scientific journal articles discussing digital literacy, religious literacy, and Islamic Religious Education. The collected data were then analyzed using content analysis to identify the concepts, principles, and forms of implementation of the integration of digital literacy and religious literacy in PAI materials. The results of the study indicate that the integration of digital literacy and religious literacy in PAI materials combines digital competencies with an understanding of Islamic values so that students are able to critically understand Islamic teachings, respond wisely to religious information in digital media, and apply it responsibly. This integration is implemented through the use of digital technology, the reinforcement of digital ethics based on Islamic values, the development of skills in analyzing religious information, and the active role of teachers as learning facilitators.